An exploration of employee readiness for change at Walter Sisulu University - Mpepo, Bulelwa N (Rhodes University, Faculty of Commerce, Rhodes Business School, 2017)
Higher education institutions are faced with pressure to change to meet academic as well as socio-economic needs. These changes are often aimed at achieving financial viability, increased institutional efficiency, and solving problems of fragmentation in the university. Universities can change in their structure, operations, systems, or and in the use or adoption of technology. The effective implementation and management of these requisite changes is the key challenge to organisations facing change. Walter Sisulu University, a comprehensive university in the Eastern Cape, has formulated a strategy to turn the university around. Included in the strategy is a project on the academic enterprise. The level of readiness for change is viewed to be a determining factor in making any change successful. Since readiness is not automatic, there is a need to prepare individuals to have a positive attitude towards the change and to embrace the proposed change initiative. This study is informed by the quest to know what will encourage and prepare employees for the implementation of the new Programme and Qualification Mix (PQM) at the University. The study therefore sought as its main purpose to explore factors influencing individual readiness for change in the PQM at Walter Sisulu University. A qualitative approach was adopted in the study. Models of change readiness were reviewed to identify themes that would be used to explore the levels of readiness amongst university academic employees who were to implement the new Programme and Qualification Mix. Documents were analysed to understand the change in PQM and face-to-face, semi-structured interviews held to solicit the views of academic employees regarding enablers or inhibiters of their readiness. Results highlighted the poor preparation of academic employees at Walter Sisulu University to support and implement the change. Key concerns of employees included dissatisfaction with the inadequate and inappropriate communication strategies, uncertainty about the suitability of the changed PQM, doubt regarding leadership support for change, as well as the perceived risk of the change. However, the main enablers were the comprehension by WSU employees of the need for a new PQM to address the poor alignment with university vision and HEQSF requirements, an appreciation of the lack of social relevance of the programmes, and confidence that they have the requisite skills and qualifications. The perceived benefits for the institution provided the needed spur for embracing the new PQM.
Keywords: Walter Sisulu University for Technology & Science -- Employees -- Attitudes; Education, Higher -- South Africa -- Case studies; Educational change -- South Africa -- Case studies; Organizational change -- South Africa -- Case studies; Programme and qualification mix